The neighbourhood effects of geographical access to tobacco retailers on individual smoking behaviour. Issue 1 (15th July 2008) - Pearce, J; Hiscock, R; Moon, G; Barnett, R
Abstract : Objective: To investigate whether neighbourhood measures of geographical accessibility to outlets selling tobacco (supermarkets, convenience stores and petrol stations) are associated with individual smoking behaviour in New Zealand. Methods: Using geographical information systems, travel times from the population-weighted centroid of each neighbourhood to the closest outlet selling tobacco were calculated for all 38 350 neighbourhoods across New Zealand. These measures were appended to the 2002/03 New Zealand Health Survey, a national survey of 12 529 adults. Two-level logistic regression models were fitted to examine the effects of neighbourhood locational access upon individual smoking behaviour after controlling for potential individual- and neighbourhood-level confounding factors, including deprivation and urban/rural status. Results: After controlling for individual-level demographic and socioeconomic variables, individuals living in the quartiles of neighbourhoods with the best access to supermarkets (OR 1.23, 95% CI 1.06 to 1.42) and convenience stores (OR 1.19, 95% CI 1.03 to 1.38) had a higher odds of smoking compared with individuals in the worst access quartiles. However, the association between neighbourhood accessibility to supermarkets and convenience stores was not apparent once other neighbourhood-level variables (deprivation and rurality) were included. Conclusions: At the national level, there is little evidence to suggest that, after adjustment for neighbourhood deprivation, better locational access to tobacco retail provision in New Zealand is associated with individual-level smoking behaviour.